LIMPID: a versatile method for visualization of brain vascular networks. (17th February 2021) - Xie, Wenguang; Gong, Xiao-Ting; Cheng, Xiaofeng; Cao, Jingjing; Zhao, Jin; Zhang, Hao-Li; Zhang, Shengxiang
Abstract : Amino-functionalized and fluorescence-labeled nanoparticles were used to label blood vessels in the brain. This method achieved stable labeling of cerebrovascular networks and was compatible with tissue clearing and multi-channel imaging. Abstract : Visualization of cerebrovascular networks is crucial for understanding the pathogenesis of many neurological diseases. Recently developed optical clearing techniques offer opportunities in deep tissue imaging, and have been successfully applied in many research studies. The development of nanotechnology enables the labeling of brain vessels with functionalized micro/nanoparticles embedded with fluorescent dyes. We herein report an efficient method, named LIMPID (Labeled and Interlinked Micro/nanoparticles for Imaging and Delipidation), specific for the precise fluorescence imaging of vascular networks in clearing-treated tissues. This robust vessel labeling technique replaces conventional fluorescence dyes with functionalized polymer micro/nanoparticles that are able to cross-link with polyacrylamide to form dense hydrogels in vessels. LIMPID shows high-robustness during the clearing process without sacrificing fluorescence signals and clearing performance. LIMPID enables three dimension (3D) visualization of elaborate vascular networks in mouse brains and is compatible with other fluorescence-labeling techniques. We have successfully applied this method to acquire cortical vasculature images simultaneously with the neurons or microglia, as well as to evaluate vascular damage in a mouse model of stroke. The LIMPID method provides a novel tool for the precise analysis of vascular dysfunction and vascular diseases.